Hormonal activation of let-7-C microRNAs via EcR is required for adult Drosophila melanogaster morphology and function. - Chawla, G.; Sokol, N.S. (Development, 2012)
Steroid hormones and their nuclear receptors drive developmental transitions in diverse organisms, including mammals. In this study, we show that the Drosophila steroid hormone 20-hydroxyecdysone (20E) and its nuclear receptor directly activate transcription of the evolutionarily conserved let-7-complex (let-7-C) locus, which encodes the co-transcribed microRNAs miR-100, let-7 and miR-125. These small RNAs post-transcriptionally regulate the expression of target genes, and are required for the remodeling of the Drosophila neuromusculature during the larval-to-adult transition. Deletion of three 20E responsive elements located in the let-7-C locus results in reduced levels of let-7-C microRNAs, leading to neuromuscular and behavioral defects in adults. Given the evolutionary conservation of let-7-C microRNA sequences and temporal expression profiles, these findings indicate that steroid hormone-coupled control of let-7-C microRNAs is part of an ancestral pathway controlling the transition from larval-to-reproductive animal forms.